Запровадження проєкту «Поліцейський офіцер громади» як крок у напрямі зміцнення місцевої інфраструктури безпеки - Безпалова, О. І.; Bezpalova, O. I.; ORCID: http://orcid.org/0000-0003-2886-695X; ResearcherID: J-7221-2016 (Право і безпека. - 2020. - № 1 (76). - С. 13-18, 2020)
Акцентовано увагу на тому, що основною метою проєкту «Поліцейський офіцер громади» є забезпечення тісної взаємодії поліцейських з об’єднаною територіальною громадою, орієнтація діяльності поліцейських, у першу чергу, саме на потреби громади. Розкрито особливості цього проєкту. Окреслено ключові етапи реалізації проєкту «Поліцейський офіцер громади». Охарактеризовано особливості підготовки поліцейських офіцерів громади, оскільки саме від цього безпосередньо залежить ефективність виконання ними покладених на них обов’язків та стан публічного порядку і безпеки в межах конкретної об’єднаної територіальної громади. Наголошено на важливості розробки положення з організації роботи поліцейських офіцерів громади та вироблення дієвого механізму розробки навчальних програм для підготовки поліцейських офіцерів громади.

The author has emphasized on the importance of strengthening the institutional capacity of local self-government agencies to address their challenges, including in the field of public safety, in particular by strengthening local security infrastructure. It has been stated that the urgent issue of the present time is to update the tools of interaction between the local population and the police to achieve a common goal – to ensure public order and safety at the regional level focused on the needs of citizens. It has been emphasized that it is currently important to use the positive foreign experience of organizing the work of the police agencies and units. On the basis of studying this experience it is advisable to implement pilot projects aimed at creating a safe environment for citizens, which should implement effective local security infrastructure. To this end, the project “Community Police Officer” was launched in 2019 as part of the reform of the National Police in Ukraine. Particular attention has been paid to the fact that the main purpose of the project “Community Police Officer” is to ensure close cooperation between police officers and amalgamated community, where police activities are primarily focused on the needs of the community. It has been argued that a characteristic feature of the project “Community Police Officer” is the focus on the introduction of a qualitatively and meaningfully new format of policing, where the needs of the community, local population should be in priority, which should be studied and ensured by keeping constant contacts between police officers and local population. The main innovations of this project have been analyzed. The powers of the community police officer and the district police officer have been differentiated. The key stages of the project “Community Police Officer” have been outlined. Specific features of training community police officers have been characterized, since it directly affects the effectiveness of their duties and the state of public order and safety within a particular amalgamated community. The peculiarities of evaluating the effectiveness of the community police officer’s work have been revealed. The author has emphasized on the importance of developing Regulations on the organization of community police officers’ work and developing an effective mechanism for elaborating the training programs for community police officers.

Акцентировано внимание на том, что основной целью проекта «Полицейский офицер общества» является обеспечение тесного взаимодействия полицейских с объединенной территориальной общиной, ориентация деятельности полицейских, в первую очередь, именно на нужды общины. Раскрыты особенности данного проекта. Определены ключевые этапы реализации проекта «Полицейский офицер общины». Охарактеризованы особенности подготовки полицейских офицеров общины, поскольку именно от этого напрямую зависит эффективность выполнения ими возложенных на них обязанностей и состояние общественного порядка и безопасности в пределах конкретной объединенной территориальной общины. Подчеркнута важность разработки положения по организации работы полицейских офицеров общины и выработки действенного механизма разработки учебных программ для подготовки полицейских офицеров общины.
Introduction of the project “Community police officer” as a step towards strengthening local security infrastructure
Введение проекта «Полицейский офицер общины» как шаг в направлении укрепления местной инфраструктуры безопасности
Безпалова, О. І. Запровадження проєкту ‘Поліцейський офіцер громади’ як крок у напрямі зміцнення місцевої інфраструктури безпеки / Ольга Ігорівна Безпалова // Право і безпека. - 2020. - № 1 (76). - С. 13-18. - DOI: https://doi.org/10.32631/pb.2020.1.01.
Безпалова, О. І. (2020) «Запровадження проєкту ‘Поліцейський офіцер громади’ як крок у напрямі зміцнення місцевої інфраструктури безпеки», Право і безпека, 76(1), с. 13-18. doi: 10.32631/pb.2020.1.01.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; поліція; поліцейський офіцер громади; об’єднана територіальна громада; місцева інфраструктура безпеки; публічний порядок; публічна безпека; проєкт «Поліцейський офіцер громади»; police; community police officer; amalgamated community; local safety infrastructure; public order; public security; полиция; полицейский офицер общины; объединенная территориальная община; местная инфраструктура безопасности; публичный порядок; общественная безопасность